Long-term air temperature trends in Somalia from 1901 to 2021 - Alasow, Ahmed Abdiaziz; Hersi, Abdifatah Ahmed; Nadarajah, Saralees; Omar, Abdillahi Osman; Ashaari, Zulfa Hanan; Warsame, Abdimalik Ali (Springer, 2024)
This study analyzed long-term temperature trends in Somalia from 1901 to 2021 using monthly Climate Research Unit (CRU) data. Time series analysis, including Mann-Kendall trend tests and linear regression, was applied to examine temperature patterns. The findings revealed a consistent warming trend of 0.0039 °C /decade, with acceleration in recent decades. Monthly temperature distributions showed clear seasonal patterns, with the warmest period occurring from March to May (27.5–28 °C median) and the coolest in December and January (around 25 °C median). Extremely high temperature events, defined as those exceeding the 95th percentile, increased in frequency and intensity, particularly from the 1980s onwards, with some events exceeding 29 °C. Spatial analysis using inverse distance weighting and k-means clustering identified distinct temperature clusters across Somalia, highlighting regional variability. The annual temperature range showed a slight increasing trend from 2.3 °C to 4.6 °C, suggesting greater temperature fluctuations within years. Seasonal analysis found spring and summer had the most pronounced warming trends, with spring temperatures rising from 27 °C to 28.5 °C during the study period. The warmest decade was observed in the 2010s, with mean temperatures reaching 27.1 °C, underscoring the recent intensification of warming.